State of the art of IPv6 conformance and interoperability testing. - Vallejo, Alex (IEEE Communications magazine)
Since the publication of William Stallings's article "IPv6: The New Internet Protocol" in the IEEE Communications Magazine ten years ago, IPv6 protocol has evolved greatly and is currently supported by the main basic software and hardware implementations present in principal worldwide networks. In this article we analyze the formal status of IPv6 from different points of view. First, we present the main forces behind the development of the implementations that support IPv6 and the promotion of this technology. We then review the various conformance and interoperability testing initiatives with a special emphasis on the IPv6 Ready Logo Program. Finally, we analyze the state of the art of the certified IPv6 market implementations.